Adoption of agricultural technologies among rice farmers in Benin - Nonvide, Gbêtondji Melaine Armel (My University, 2021)
Adoption of agricultural technologies in Benin remains at a very low level. This paper analyzes the factors that determine the adoption of agricultural technologies by rice producers in Benin. It employs a simple probit and Poisson regression models, as well as a multivariate probit model to account for the unobserved interaction between technology adoption decisions. Results reveal that variables such as education, access to extension services, membership of a farmers-based organization, access to credit, media and use of a mobile phone are important in the process of increasing adoption of agricultural technologies. These variables must be taken into consideration in the elaboration of the agricultural modernization policy
Keywords: adoption; agricultural technologies; Benin; multivariate probit model; rice